Analisis Hasil Uji Lentur Penampang Silindris Baja Karbon, Penampang Persegi Empat Kayu Usuk, Paving Stone, dan Bata Ringan - Muchamad Fachryan Winata; Syamsul Hadi; Ilham Fadilla Kusuma; Wira Atha' Dzakwan Firdaus; Bagus Aditya Nurhidayat; Ahmed Ibn Fadhlan; Salwa Najma Fahira (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2026)
The unknown exact flexural strength of low carbon steel, Randu ribs wood, paving stones, and lightweight bricks is a problem faced. The purpose of this research is to obtain the flexural strength of low carbon steel, Randu ribs, paving stones, and lightweight bricks. The research method is carried out through the preparation of low carbon steel specimens 16mmx200mm, Randu ribs 40mmx60mmx250mm, paving stones 55mmx100mmx200mm, lightweight bricks 95mmx100mmx300mm, Tarno Grocky flexural testing machine settings, flexural testing support distance for low carbon steel 160mm, Randu ribs 220mm, paving stones 170mm, and lightweight bricks 260mm, flexural testing of each material, making flexural stress and deflection curves for low carbon steel, and analyzing flexural test results. The results of the study showed that the flexural strength of low carbon steel was 698 MPa at a deflection of 1.1 mm, the flexural strength of Randu rib wood in an upright position was 40.7 MPa, in a horizontal position was 55.5 MPa, in a normal position of paving stone in an upper position (normal) was 6.64 MPa, in a lower position (upside down) was 6.62 MPa, and in a lightweight brick was 1.28 MPa, which implies that the type of material, the distance between supports and the cross-section of the specimen greatly affect its flexural strength, except for ductile materials for low carbon steel which do not have flexural strength, but have yield strength at a certain deflection.